Analisis Pemodelan Tsunami terhadap Perkiraan Kerusakan Infrastruktur di Kawasan Pantai Wediombo, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Octiana Lestyan Saputri; Kuswaji Dwi Priyono; Aziz Akbar Mukasyaf; Nirma Lila Anggani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Wediombo Beach area, Gunungkidul Regency, Special Region of Yogyakarta, is located within a tsunami-prone zone caused by the subduction of the Indo-Australian Plate beneath the Eurasian Plate along the Sunda Subduction Zone. This study aims to: (1) model tsunami scenarios based on wave height variations of 7 m, 14 m, and 21 m; and (2) estimate the extent of infrastructure damage under each scenario in the Wediombo Beach area. Inundation zone modeling was performed using the DEM overlay method with 30-meter resolution SRTM data in ArcGIS, while infrastructure damage estimation followed the classification framework proposed by Schneider, Hoffmann, and Reicherter (2016), based on elevation and distance-to-coastline parameters. Infrastructure data were obtained through OpenStreetMap (OSM) digitization and validated by field surveys covering 64 infrastructure units. The modeling results indicate inundation areas of 0.023600 km² (7 m scenario), 0.032215 km² (14 m scenario), and 0.037193 km² (21 m scenario). Of the 64 infrastructure units analyzed, 51 units (79.69%) are potentially affected, comprising 23 units (44.23%) with severe damage, 15 units (28.85%) with moderate damage, and 14 units (26.92%) with minor damage. Economic infrastructure exhibits the highest impact rate (91.18%), whereas all transportation infrastructure remains unaffected across all three scenarios, indicating its strategic role as evacuation routes. These findings provide a scientific basis for tsunami hazard zonation and the formulation of coastal spatial planning policies in the Wediombo Beach area.